2022
DOI: 10.3389/fmicb.2022.970139
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and transcriptomic analyses revealed gene networks involved in heightened resistance against tomato yellow leaf curl virus infection in salicylic acid and jasmonic acid treated tomato plants

Abstract: Tomato yellow leaf curl virus (TYLCV), a member of the genus Begomovirus of the Geminiviridae family, causes leaf curl disease of tomato that significantly affects tomato production worldwide. SA (salicylic acid), JA (jasmonic acid) or the JA mimetic, COR (coronatine) applied exogenously resulted in improved tomato resistance against TYLCV infection. When compared to mock treated tomato leaves, pretreatment with the three compounds followed by TYCLV stem infiltration also caused a greater accumulation of H2O2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…Considering that the ability of resistance of some tomato cultivar has decreased because of many physiological races of C. fulvum rapidly mutated, we focused on investigating the transcriptome profiles during early stage of interaction with C. fulvum in tomato leaves by using susceptible tomato plants ( Jiang et al., 2022b ). As we expected, a variety of defense related genes are identified after C. fulvum inoculation, such as PR1 , HSP90 , and WRKY1 , which is consistence with the previous findings ( Zhao et al., 2019 ; Wang et al., 2022 ). Based on previous reported that flg22 (flagellin 22) binding induces FLS2-BAK1 (BRI1-associated kinase1) heteromerization to activate immune responses in Arabidopsis thaliana ( Sun et al., 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Considering that the ability of resistance of some tomato cultivar has decreased because of many physiological races of C. fulvum rapidly mutated, we focused on investigating the transcriptome profiles during early stage of interaction with C. fulvum in tomato leaves by using susceptible tomato plants ( Jiang et al., 2022b ). As we expected, a variety of defense related genes are identified after C. fulvum inoculation, such as PR1 , HSP90 , and WRKY1 , which is consistence with the previous findings ( Zhao et al., 2019 ; Wang et al., 2022 ). Based on previous reported that flg22 (flagellin 22) binding induces FLS2-BAK1 (BRI1-associated kinase1) heteromerization to activate immune responses in Arabidopsis thaliana ( Sun et al., 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have highlighted the involvement of various phytohormones, such as salicylic acid (SA), jasmonic acid (JA), ethylene, auxin, cytokinin, gibberellic acid, brassinosteroids and abscisic acid, in plant–geminivirus infection [ 10 , 128 ]. The use of exogenous SA and JA improves resistance to TYLCV infection in plants [ 129 ]. SA, ethylene and cytokinin pathways genes are upregulated within geminivirus infections [ 85 , 130 , 131 , 132 , 133 ].…”
Section: Hormone-mediated Defense Against Geminivirusmentioning
confidence: 99%